2011
DOI: 10.1021/am200246n
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Zwitterionic Poly(dimethylsiloxane) (PDMS)-Contained Poly(Ether amine) (Z-SiPEA) as the Responsive Polymeric Dispersant

Abstract: We demonstrated here a novel concept of the responsive dispersant based on the amphiphilic zwitterionic poly(ether amine) (Z-SiPEAs), which can control the dispersion of dyes and pigments in water. Z-SiPEAs are composed of short poly (dimethylsiloxane) (PDMS) chain in the backbone and Jeffamine L100 as graft chain. The amino groups in the backbone and carboxyl groups grafted to the backbone make the obtained Z-SiPEAs zwitterionic. Transmission electron microscopy (TEM) and dynamic light scattering (DLS) result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…6,7 Therefore, the resulting hybrid matrix can exhibit enhanced adsorption capacity and incorporate a large number of species. [8][9][10][11] These authors developed hyperbranched poly(etheramine) (hPEA) hybrids for selective dye adsorption and separation. [8][9][10][11] These authors developed hyperbranched poly(etheramine) (hPEA) hybrids for selective dye adsorption and separation.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Therefore, the resulting hybrid matrix can exhibit enhanced adsorption capacity and incorporate a large number of species. [8][9][10][11] These authors developed hyperbranched poly(etheramine) (hPEA) hybrids for selective dye adsorption and separation. [8][9][10][11] These authors developed hyperbranched poly(etheramine) (hPEA) hybrids for selective dye adsorption and separation.…”
Section: Introductionmentioning
confidence: 99%
“…Table 7 shows the results of different tests. 22 H. In this case poly(vinyl alcohol) in combination with nonionic surfactants make up the disperse system with the lowest stability. On the basis of the conducted tests, it may ve said that the higher dispersion efficiency is associated with the larger pigments specific surface area and a lower amount of concentrator and surfactant.…”
Section: Resultsmentioning
confidence: 99%
“…Macro-chains of the concentrator interact with the surfactant adsorption layer and the more intensive it is, the higher its boundary viscosity number is. It was found, that C 17 H 34 EO 18 OH and C 17 H 35 NHEO 22 H with carboxylmethyl cellulose sodium salt are the surfactants with the highest stabilizing effect on aqueous dispersion of pigments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Jiang et al . synthesised amphiphilic zwitterionic poly(etheramine), which showed excellent dispersing ability for inorganic pigments and Hao et al . have shown that SMA has efficiency as a dispersant for organic pigments.…”
Section: Introductionmentioning
confidence: 99%